Engineering Technology Students’ Attitudes towards Engagement in Mathematics - Hamzah, Khairum; Kashi'ie, Najiyah Safwa; Waini, Iskandar; Zainal, Nurul Amira; Hairol Anuar, Siti Haryanti; Hussin, Nor Hafizah (IOSR, 2014)
The objective of this study is to understand and examine the attitudes of Engineering Technology (ET) students towards engagement in mathematics during their studies at the Faculty of Engineering Technology (FTK), Universiti Teknikal Malaysia Melaka (UTeM). In the study, a set of questionnaire that covers the questions on the students’ attitudes towards engagement in mathematics was utilized. A total of 332 second year ET students at FTK, UTeM were requested to complete this set of questionnaire during the final week of semester two for 2013/2014 session. From the findings, a conclusion has been drawn regarding the attitudes of the ET students towards engagement in mathematics. The result showed that most of the ET students were very engaged in mathematics, and their engagement was more on behavioral types during the learning process of mathematics in class at FTK, UTeM.